Sweetest Songs That Tell of the Saddest Thought (Arnold’S Personal Elegies): Exploring Arnold's Personal Elegies (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Poetry, an interpretation of life throughimagination and feeling is broadly of two kinds; personal and impersonal, thepersonal is further divided and one of his most important divisions is theelegy.  Elegy is a “mournful,melancholic, or plaintive poem especially a funeral song or a lament for thedeal”1  (Jess Stein)